The Limits of Digital Fiscal Reform: Implementation Depth of Local Government Transaction Electronification (ETPD) and Local Revenue Optimisation in Simalungun Regency - Elly Ermawati Sagala; Tunggul Sihombing; Gauri Sudhanwa Kopardekar; Arga Abdi Rafiud Darajat Lubis (International Journal Of Economics Social And Technology, 2026)
This study examines the implementation depth of Local Government Transaction Electronification (ETPD) in strengthening regional tax and levy collection in Simalungun Regency, Indonesia. It addresses a practical and theoretical paradox in digital fiscal reform: while Simalungun has demonstrated strong formal commitment to regional digitalisation through TP2DD coordination, non-cash payment channels, and institutional support, the substantive optimisation of local revenue remains uneven across agencies, revenue categories, and end users. Using a qualitative descriptive case-study design, this study involved sixteen purposively selected informants, including TP2DD leaders, relevant district agencies, a Bank Indonesia representative, sub-district revenue treasurers, and residents who had not yet adopted digital payment for local obligations. Data were collected through semi-structured interviews, field observation, and document review, then analysed using the Miles, Huberman, and Saldaña interactive model with Edward III’s implementation framework. The findings show that ETPD has contributed to administrative modernisation and wider non-cash payment availability. During the implementation period, combined regional tax and levy revenue increased from IDR 105.76 billion in 2022 to IDR 119.82 billion in 2023 and IDR 154.93 billion in 2024. However, the fiscal improvement was driven far more strongly by taxes than by levies, indicating that digital fiscal reform produces uneven effects when revenue objects differ in administrative visibility, transaction value, and collection routines. Implementation remains constrained by uneven public communication, limited technical competence among some field implementers, unequal internet access, incomplete transaction-recording devices, and low digital literacy among some community groups. The study concludes that ETPD in Simalungun represents an advancing but not yet fully consolidated reform. Its effectiveness depends not merely on payment-channel digitalisation, but on the alignment of bureaucratic capacity, transaction-monitoring infrastructure, field-level support, and user readines